ANCIENT AND MEDIEVAL ZOOMORPHIC METAL PRODUCTS OF KHOREZM - Davletmuratov, Kuralbay (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article analyzes zoomorphic metal products found in ancient and medieval monuments of Khorezm. Similar species have been found in neighboring regions. Based on the pre-Islamic religious beliefs and mythology of the peoples of the region, the symbolic content of zoomorphic objects was highlighted. The functions of zoomorphic products were also studied. Through their study, the applied arts and mythology of the ancient and medieval peoples of Khorezm and the Southern Aral Sea region have been enriched with historical data.